Sustainability Driven Strategy for Achieving Sustainable Infrastructure: Musaimeer Pumping Station and Outfall Project - Ersenkal, Dila; Peach, Gary; Paskova, Biliana (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
The increasing emphasis on global sustainability issues such as climate change, loss of biodiversity, deforestation, and water scarcity has provided a strong mandate for the construction industry to incorporate sustainable practices, more efficient processes and innovative technologies to deliver sustainable project outcomes. Implementing sustainability rating and assessment schemes throughout the lifecycle of projects has been instrumental in achieving high levels of environmental and social performance. This paper presents a case study; the Musaimeer Pumping Station and Outfall (MPSO) project, a strategic asset for Qatar, and discusses the sustainability strategy adopted for achieving the 'Very Good' level Civil Engineering Environmental Quality and Assessment Award Scheme (CEEQUAL) certification for the project. The paper sets out how the project's registration with CEEQUAL International resulted in achievement of sustainability best practice in design and construction phases. Specific achievements with regards to the key CEEQUAL topic areas including project strategy, project management, people and communities, land use and landscape, historic environment, ecology and biodiversity, water environment, physical resources use and management (such as energy, water, materials), and transport are also highlighted in this paper. The paper also provides the importance of the adopted strategy in translating the overarching Qatar National Vision 2030 and alignment with the United Nations (UN) Sustainable Development Goals (SDGs). The challenges faced throughout the project lifecyle and the benefits achieved by undertaking a CEEQUAL assessment for this project are also discussed in this paper.